Tree Induced Suction On Slope Stabilization Analysis - Mohd Fakhrurrazi, Ishak; Nazri, Ali; Azman, Kassim (Asian Research Publishing Network (ARPN), 2016)
This research explores the effect of active root zone related to slope stabilization. The matric suction produced by mature tree was determined with high and moderated intensity of rainfall event condition. The increasing of soil moistureand pour water pressure can significantly reduce shear strength of soil, which leads to shallow slope failure. This exploration is concentrate at active root zone of the tree at toe of the slope. The effect only focused on hydrological aspect with soil suction pattern within vicinity of the tree. The monitoring result show a substantially increase in soil suction at slope with tree at toe. The effect of tree water uptake on soil suction distribution is applied for slope stability analysis that significantly changes stability of the slope. The rainfall events also lead to variation on soil suction and factor of safety of the slope. The influence of water uptake from root activity at the toe of slope created a dry condition and substantially increased the factor of safety against slope failure up to 63%